Negative Consequences of Genocide on the Civilization of South Kurdistan (1983-1988) - صاڵح, م.د.ڕێواس فتاح محمد صاڵح (Sulaimani Journal for Humanities, 2024)
Genocide is considered one of the most heinous and dangerous crimes committed by the Ba'athist regime against the Kurdish people in Southern Kurdistan. This crime left deep and lasting scars on Southern Kurdistan society. This research sheds light on the negative repercussions of the Barzani genocide, the Anfal campaign, and the chemical attacks on the cultural landscape of Halabja, which targeted not only the Kurdish people but also extended their impact to the entire region. This research consists of three main sections: Section One: Physical and biological genocide and its impact on the cultural landscape of Southern Kurdistan during the period (1983-1988). Section Two: The repercussions of economic genocide in Southern Kurdistan. Section Three: Cultural genocide and its impact on Southern Kurdistan society. Finally, the findings of this study are presented.
Keywords: Genocide; Anfal; Chemical Attack; South Kurdistan; Civil Situation